Blind joint angle and delay estimation method in uniform circular array - ZHANG Xiao-fei1; XU Da-zhuan1 (Tongxin xuebao)
A novel blind joint angle and delay estimation method in uniform circular array based on trilinear model was presented. Oversampled signal of array antennas was processed by fast Fourier transform, and showed that the FFTed signal has trilinear model characteristics. A blind joint angle and delay estimation method （BJADE） in uniform circular array was proposed. This method firstly used trilinear alternating least square （TALS） algorithm to estimate the direction and delay matrices, secondly delays were estimated according to Vandermonde characteristics of delay matrix and least square principle, and DOAs were estimated according to characteristics of direction matrix and least square principle. The simulation results reveal that BJADE algorithm has the better estimation performance for delay and DOA, and it works well in the overload system. Finally, this algorithm has blind and robust characteristic, which does not need the channel impulse response.